Regional Integration and Development Asymmetries - Ryszard Rapacki (Elements of Regional Integration. A Multidimensional Approach, 2008)
The aim of the present contribution is two-fold. First, we are going to briefly overview the theoretical arguments suggesting that regional economic integration may enhance the process of real economic convergence or catching up by less-advanced members of integration arrangements towards the development levels prevailing in more advanced member countries. Second, as an empirical test of the foregoing theoretical claims, we will embark on an analysis of actual economic growth paths of the present member countries of the enlarged European Union – both the `old' (i.e. EU-15) and `new' ones that is ten transition economies from East-Central Europe who joined the EU in 2004 or 2007, respectively (CEE-10 or EU-10). In particular, we will try to show that the process of regional integration in Europe tended as a rule to enhance the real economic convergence of income levels both within the EU-15 group as well as between the new (EU-10) and the old (EU-15) member countries.
Keywords: F15; O1; 330; regional integration; development; regional integration; development